2013
DOI: 10.1177/0021998313509863
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic elasto-viscoplastic damage model for glass-fiber-reinforced polyurethane foam

Abstract: The aim of the present study was to propose a unified anisotropic elasto-viscoplastic damage model and computational analysis method for predicting the damage growth and material behavior of initially anisotropic glass-fiber-reinforced polyurethane foam (RPUF). A plasticity damage mechanism-based mechanical model with no yield surface is introduced. To consider the microcrack closure effect according to different loading directions, two types of elasto-viscoplastic damage models were developed. The developed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…Generally, the mechanical strength of the PUF is improved by including a filler material during its fabrication. In previous studies, diverse additives such as glass fibers, [19][20][21][22][23] carbon, 11,24,25 silica, 26 graphene, 27 and nanoparticles 28 have been applied as filler material. For example, Yu et al 19 showed that adding 10 wt% of chopped fiber to PUF improves the mechanical strength by 50% at cryogenic temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the mechanical strength of the PUF is improved by including a filler material during its fabrication. In previous studies, diverse additives such as glass fibers, [19][20][21][22][23] carbon, 11,24,25 silica, 26 graphene, 27 and nanoparticles 28 have been applied as filler material. For example, Yu et al 19 showed that adding 10 wt% of chopped fiber to PUF improves the mechanical strength by 50% at cryogenic temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…A three-dimensional constitutive model was derived by Iwamoto [ 20 ] based on a four-element model with an elastic series element, which was implemented into the user subroutine user defined material subroutine (UMAT) of ABAQUS/Explicit to simulate the quasi-static and dynamic compression behavior of carboxy-terminal butadiene-acrylonitrile(CTBN)-modified epoxy resin. Lee et al [ 21 ] proposed a unified anisotropic elasto-viscoplastic damage model and the relevant computational analysis was accomplished by ABAQUS to predict the damage growth and material behavior of glass-fiber-reinforced polyurethane foam (RPUF). Wang et al [ 22 ] applied a damage-modified ZWT nonlinear viscoelastic constitutive model to LS-DYNA, which was used to simulate the damage and failure of a windshield under a bird strike effectively.…”
Section: Introductionmentioning
confidence: 99%
“…, LNG CCS용 PUF를 대상으로 상온 정적 하중 조건에서 기계적 거동을 물리적으로 표현하기 위한 이방 성 점탄소성 손상 모델에 대한 연구가 있었다 (Lee et al, 2012…”
unclassified